Dry Matter Partitioning, Nutrient Content and Uptake by Colocynth (Citrullus colocynthis L.) in Relation to Spacing and Nitrogen under Rainfed Conditions - Kumawat, R N; Mahajan, S S; Mertia, R S (Annals of Arid Zone, 2016)
A field experiment was conducted during the kharif seasons of 2005 and 2006 at Chandan Farm, CAZRI, RRS, Jaisalmer, to study the effect of row spacing and nitrogen levels on dry matter partitioning, nutrient content and uptake of colocynth. The total dry matter accumulation and its distribution in leaf, vine, rind, pulp, cotyledon and testa was significantly higher in plants sown at 75 cm over 50 and 150 cm spacings. The oil content in seed and oil yield (kg ha-1 ) increased at 75 cm spacing by 2.3% and 16.1%, respectively, over 50 cm plant spacing. The contents of Nand P in all plant parts increased significantly with gradual increase in spacing from 50 to 150 cm. The uptake of Nand P was significantly higher at 75 cm spacing. Application of 40 kg N ha-1 increased total dry matter production from 1388 to 2251, dry fruit yield from 590 to 1256, seed yield from 264 to 509 and oil yield from 71 to 128 kg ha-1 over control and significantly increased content of Nand P in leaf, vine, rind and cotyledon and uptake of Nand P. r Key words: Colocynth, dry matter, nitrogen, nutrient content and uptake, spacing.